Microsoft Azure fundamentals certification and beyond : simplified cloud concepts and core Azure fundamentals for absolute beginners to pass the AZ-900 exam - Miles, Steve (Packt Publishing, 2022)
Gain in-depth knowledge of Azure fundamentals that will make it easy for you to achieve AZ-900 certification About This Audiobook Get fundamental knowledge of cloud concepts and the Microsoft Azure platform Explore practical exercises to gain experience of working with the Microsoft Azure platform in the real world Prepare to achieve AZ-900 certification on the first go with the help of simplified examples covered in the book In Detail This is the digital and cloud era, and Microsoft Azure is one of the top cloud computing platforms. It's now more important than ever to understand how the cloud functions and the different services that can be leveraged across the cloud. This book will give you a solid understanding of cloud concepts and Microsoft Azure, starting by taking you through cloud concepts in depth, then focusing on the core Azure architectural components, solutions, and management tools. Next, you will understand security concepts, defense-in-depth, and key security services such as Network Security Groups and Azure Firewall, as well as security operations tooling such as Azure Security Center and Azure Sentinel. As you progress, you will understand how identity, governance, privacy, and compliance are managed in Azure. Finally, you will get to grips with cost management, service-level agreements, and service life cycles. Throughout, the book features a number of hands-on exercises to support the concepts, services, and solutions discussed. This provides you with a glimpse of real-world scenarios, before finally concluding with practice questions for AZ-900 exam preparation. By the end of this Azure book, you will have a thorough understanding of cloud concepts and Azure fundamentals, enabling you to pass the AZ-900 certification exam easily. Audience This Azure fundamentals book is both for those with technical backgrounds and non-technical backgrounds who want to learn and explore the field of cloud computing, especially with Azure. This book will also help anyone who wants to develop a good foundation for achieving advanced Azure certifications. There is no prerequisite for this book except a willingness to learn and explore cloud concepts and Microsoft Azure.